EKSISTENSI PEREMPUAN PADA TRADISI PERKAWINAN ADAT ENDE DALAM PERBANDINGAN DENGAN KONSEP DASEIN MARTIN HEIDEGGER - Bato, Kamilus (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This article aims to study the concept and understanding of Ende traditional marriage traditions that have been carried out since their ancestors until today. Apart from that, the author tries to make a comparison between the existence of women in the Ende traditional marriage tradition and the understanding of the concept of Dasein put forward by Martin Heidegger. In this paper, the author uses the observation method, interview method, and also the literature analysis method. Apart from that, the theories used by the author are always based on the thought concepts of Martin Heidegger. This article should examine or talk in more detail about the concepts of marriage in Ende society and also the concepts of Heidegger's thinking about Dasein as a way of being in the world and involving oneself in being actively involved, living and working in the world. The existence of women in this paper is greatly influenced by cultural factors such as belis or dowry, which can then determine the existence and way of being in a man's family. Therefore, the author examines in more detail and detail in this article the concept of Dasein and women's way of being in the middle of the world or